2009
DOI: 10.1021/jf803421w
|View full text |Cite
|
Sign up to set email alerts
|

Detection of arc Genes Related with the Ethyl Carbamate Precursors in Wine Lactic Acid Bacteria

Abstract: Trace amounts of the carcinogen ethyl carbamate can appear in wine by the reaction of ethanol with compounds such as citrulline and carbamyl phosphate, which are produced from arginine degradation by some wine lactic acid bacteria (LAB). In this work, the presence of arc genes for the arginine-deiminase pathway was studied in several strains of different species of LAB. Their ability to degrade arginine was also studied. To detect the presence of arc genes, degenerate primers were designed from the alignment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 50 publications
(54 reference statements)
2
24
0
2
Order By: Relevance
“…The ability to degrade arginine and produce ethyl carbamate precursors have been found amongst both O. oeni and L. plantarum strains, although conflicting results in the literature would indicate that this ability is strain dependant. In addition, this characteristic also seems to be more widespread amongst O. oeni strains, compared to L. plantarum (Liu et al, 1994(Liu et al, , 1995Mira de Orduña et al, 2000, 2001Spano et al, 2004;Uthurry et al, 2006;Araque et al, 2009;Romero et al, 2009). These findings in literature are supported by the finding in this study: six of the seven O. oeni strains were positive for arginine deiminase and carbamate kinase and all seven were positive for ornithine transcarbamylase.…”
Section: Malolactic Fermentation Must and Wine Composition Before Inosupporting
confidence: 83%
“…The ability to degrade arginine and produce ethyl carbamate precursors have been found amongst both O. oeni and L. plantarum strains, although conflicting results in the literature would indicate that this ability is strain dependant. In addition, this characteristic also seems to be more widespread amongst O. oeni strains, compared to L. plantarum (Liu et al, 1994(Liu et al, , 1995Mira de Orduña et al, 2000, 2001Spano et al, 2004;Uthurry et al, 2006;Araque et al, 2009;Romero et al, 2009). These findings in literature are supported by the finding in this study: six of the seven O. oeni strains were positive for arginine deiminase and carbamate kinase and all seven were positive for ornithine transcarbamylase.…”
Section: Malolactic Fermentation Must and Wine Composition Before Inosupporting
confidence: 83%
“…The final reaction is catalysed by carbamate kinase during which ATP is generated from carbamyl phosphate. The catabolism of arginine contributes to LAB growth due to the generation of ATP, but two of the intermediates formed, citrulline and carbamyl phosphate, are able to react with ethanol to form EC (Liu et al, 1994(Liu et al, , 1995Arena & Manca de Nadra, 2002;Volschenk et al, 2006;Araque et al, 2009). Strains of O. oeni and Lactobacillus buchneri are able to excrete citrulline and carbamyl phosphate (Liu et al, 1994;Mira de Orduña et al, 2000, 2001 and Uthurry et al (2006) also found that strains of O. oeni and L. hilgardii were able to contribute to the EC concentration.…”
Section: Ethylcarbamatementioning
confidence: 99%
“…Recently, Romero et al (2009) found L. plantarum strains in this study were unable to degrade arginine to form citrulline. Araque et al (2009) investigated the presence of genes involved in the deiminase pathway that are responsible for the degradation of arginine in different LAB species. The degrading strains included L. brevis and L. hilgardii, O. oeni, P. pentosaceus, and some strains of Leuc.…”
Section: Ethylcarbamatementioning
confidence: 99%
“…types of fermentation are the elimination of adverse interactions between bacteria and yeast and a reduction in the risk of overproduction of undesirable metabolites, such as acetic acid (related to a low concentration of residual sugars), and other metabolites, like biogenic amines and ethyl carbamate [3,22,26,27,32,40]. However, problems with the proper initiation and control of the process of wine production in the classical system have prompted a search for new alternative methods of MLF induction.…”
mentioning
confidence: 99%